Coexistence of service- and facility-based competition: The relevance of access prices for "make-or-buy"-decisions - Christian M. Bendery; Georg Goetz (International Telecommunications Society (ITS), 2015)
This paper models competition between two firms, which provide broadband In-ternet access in regional markets with different population densities. The firms, an incumbent and an entrant, differ in two ways. First, consumers bear costs when switching to the entrant. Second, the entrant faces a make-or-buy decision in each region and can choose between service-based and facility-based entry. The usual trade-off between static and dynamic efficiency does not apply in the sense that higher access fees might yield both, lower retail prices and higher total coverage. This holds despite a strategic effect in the entrant's investment decision. While investment lowers marginal costs in regions with facility-based entry, it intensifies competition in all regions. We show that the cost-reducing potential of investments dominates the strategic effect: Higher access fees increase facility-based competition, decrease retail prices and increase total demand.
Keywords: D43; L13; L51; L96; 330; Broadband access markets; facility- and service-based entry; investments; economies of density; switching costs